Placenta acretta spectrum. Case report - Rojas-Pillaca, Ramiro (2023)
Introduction. The placenta accreta spectrum is the result of a pathological invasion of the placenta into the uterus, depending on the depth and extent of the invasion; that produce clinical manifestations such as vaginal bleeding, which can end in hysterectomy and maternal death. Report. A 34-year-old pregnant patient with 31 weeks of gestation, from Ayacucho, she came for profuse vaginal bleeding and a history of two cesarean sections, for which it was decided to terminate the pregnancy and perform a hysterectomy, the diagnosis of placenta increta was confirmed by pathology. The patient evolves favorably and is discharged with outpatient control. Conclusion. The treatment of choice for placenta accreta that invades myometrium continues to be hysterectomy due to the high mortality and postpartum haemorrhage that it triggers, so early diagnosis and management is of vital importance.